Influence of gender, power, and hand position on pelvic motion during seated cycling - Sauer, J. L.; Potter, J.; Weisshaar, C. L.; Ploeg, H. L.; Thelen, D. G. (Medicine & Science in Sports & Exercise, 2007)
Introduction/Purpose: An understanding of normal pelvic motion during seated cycling is relevant to saddle design and bicycle fitting. In this study, we investigated the effects of gender, power, and hand position on pelvic motion throughout a pedal stroke. We also investigated whether anthropometric factors could explain any interindividual differences observed.